2013
DOI: 10.1093/cid/cit453
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Acute Kidney Injury With Intravenous Colistimethate Sodium Compared With Polymyxin B in Critically Ill Patients at a Tertiary Care Medical Center

Abstract: Nephrotoxicity was assessed in 173 critically ill patients receiving intravenous colistin or polymyxin B; it occurred in 60.4% and 41.8%, respectively. Further investigation is necessary to elucidate the reason for the difference in nephrotoxicity observed between the groups and to assess the impact of severity of illness and dosing/administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(157 citation statements)
references
References 19 publications
6
135
3
7
Order By: Relevance
“…y Akajagbor y cols. 15,18 , quienes documentaron en sus estudios mayor nefrotoxicidad en pacientes con creatininemia anormal al inicio del tratamiento.…”
Section: Discussionunclassified
“…y Akajagbor y cols. 15,18 , quienes documentaron en sus estudios mayor nefrotoxicidad en pacientes con creatininemia anormal al inicio del tratamiento.…”
Section: Discussionunclassified
“…Two recent comparative studies involving large numbers of patients showed that the nephrotoxicity rates were lower for polymyxin B than for CMS/colistin (59,60).…”
Section: Use Of Colistin In Human and Veterinary Medicine Use In Humamentioning
confidence: 99%
“…The dry antibacterial drug development pipeline has led to the revival of the polymyxin class of antibiotics, colistin (i.e., polymyxin E) and polymyxin B, as a last-line defense for treatment of infections caused by multidrug-resistant (MDR) Gram-negative pathogens (2,3). However, the use of polymyxins has largely been limited by nephrotoxicity, the major dose-limiting factor occurring in up to 60% of patients (4)(5)(6). As a result, development of nephroprotective agents is very important for optimizing clinical use of polymyxins.…”
mentioning
confidence: 99%